Morphology, chemistry, performance trident: Insights from hollow, mesoporous carbon nanofibers for dendrite-free sodium metal batteries. (August 2021) - Mubarak, Nauman; Rehman, Faisal; Wu, Junxiong; Ihsan-Ul-Haq, Muhammad; Li, Yang; Zhao, Yunhe; Shen, Xi; Luo, Zhengtang; Huang, Baoling; Kim, Jang-Kyo
Abstract: The potential application of metallic Na anodes for high energy density batteries is plagued by dendrite formation accompanied by rapid consumption of electrolyte and Na metal. Herein, coaxially electrospun, hollow and mesoporous carbon nanofiber (HpCNF) hosts possessing strong affinity with Na are developed for Na metal batteries. The combined in situ and cryogenic microscopy along with theoretical simulations reveal that the highly sodiophilic HpCNFs with abundant defects and nitrogen functional groups enable compact, uniform plating of Na with excellent reversibility aided by the resilient, fluorine-rich SEI layer. Thanks to the optimized Na deposition in the entire structure, the Na@HpCNF anodes present an average Coulombic efficiency of 99.7% after 1, 400 cycles at a current density of 3 mA cm −2 and a plating/striping capacity of 6 mAh cm −2 . Their symmetric cell maintains stable cycles for over 1000 hr at 5 mA cm −2 and 5 mAh cm −2, which is among the best when compared with state-of-the-art electrodes. The full cells paired with a Na3 V2 (PO4 )2 F3 cathode deliver remarkable specific capacities of 115 and 93 mAh cm −2 after 500 cycles at 1 C and 200 cycles at 4 C, respectively. These findings highlight new insight into rationally-designed metal anodes towards the development of high-performance metal batteries. Graphical Abstract: The unique hollow and mesoporous carbon nanofibers with a superior sodiophilic character enable excellent electrochemical performance for sodium metal batteries. The correlation between host structure, surface chemistry and superior electrochemical performance is revealed by real-time Na metal deposition on nanofiber cells using in situ TEM and visualization of resilient, thin, fluorine-rich SEI using cryo-EM. ga1 Highlights: Facile co-axial electrospinning approach to fabricate defect-abundant carbon hosts. In situ TEM/SAED and melt infiltration experiments verify super-sodiophilicity. Cryo - EM, depth profiling X-ray photoelectron spectroscopy and ToF-SIMS reveal a robust, thin, fluorine-rich SEI layer. DFT calculations present uniform Na plating on defective, N-functionalized C while 3D dendritic morphology for graphitic C. Exceptional electrochemical performance in half-cell, symmetric cell, and full cell configurations.